2023
DOI: 10.3389/fpsyg.2022.1044988
|View full text |Cite
|
Sign up to set email alerts
|

Too much is too little: Estimating the optimal physical activity level for a healthy mental state

Abstract: IntroductionAlthough physical activity and exercise are generally thought to have favorable effects on mental health, excessive physical activity may have unfavorable effects. In this study, the associations between physical activity and the states of mental health with U-shaped dose–response curves were hypothesized, and the ranges of physical activity resulting in optimal effects on mental health were investigated.MethodsA cross-sectional survey was conducted on 1,237 adult volunteers in 2017 and 2018. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Their research revealed an inverted-U shaped correlation between weekend physical activity and academic achievement, with a noted sex difference in the optimal duration of exercise-−2 h for males and 1 h for females. The inverted-U shape finding aligns with another recent study by Shimura et al ( 2023 ), which examined the association between the total duration of weekly physical activity and mental health outcomes. Moreover, the gender-differentiated impact in the above study is further explored by Wu et al , who found significant associations between physical activity levels and depressive symptoms in males but not in females.…”
supporting
confidence: 88%
“…Their research revealed an inverted-U shaped correlation between weekend physical activity and academic achievement, with a noted sex difference in the optimal duration of exercise-−2 h for males and 1 h for females. The inverted-U shape finding aligns with another recent study by Shimura et al ( 2023 ), which examined the association between the total duration of weekly physical activity and mental health outcomes. Moreover, the gender-differentiated impact in the above study is further explored by Wu et al , who found significant associations between physical activity levels and depressive symptoms in males but not in females.…”
supporting
confidence: 88%
“…Previous studies have indicated the existence of an optimal physical activity time regarding the influence of physical activity intensity on mental health [ 29 ]. There are also reports that this optimal physical activity time is associated with lower depressive symptoms [ 30 , 38 ]. In the present study, we hypothesized that physical activity time affects depressive symptoms via state and trait anxiety, and that an optimal physical activity time exists in this effect, and tested this hypothesis by a path analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association between physical activity and mental health has been reported in various studies, as described in the Introduction section, the dose-response relationship between physical activity and mental health has not been clarified, which makes specific interventions, such as exercise therapy, difficult. Whereas positive associations between physical activity and mental health have been reported, it was also reported that excessive physical activity levels exacerbate mental health burden as much as no physical activity at all [ 29 , 30 ]. In addition, a U-shaped association between physical activity for leisure and depressive symptoms among Japanese workers [ 38 ] was also reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations